Inhibitory masking controls the threshold sensitivity of retinal ganglion cells - Pan, Feng (J Physiol, 2016)
KEY POINTS: Retinal ganglion cells (RGCs) in dark‐adapted retinas show a range of threshold sensitivities spanning ∼3 log units of illuminance. Here, we show that the different threshold sensitivities of RGCs reflect an inhibitory mechanism that masks inputs from certain rod pathways. The masking inhibition is subserved by GABA(C) receptors, probably on bipolar cell axon terminals. The GABAergic masking inhibition appears independent of dopaminergic circuitry that has been shown also to affect RGC sensitivity. The results indicate a novel mechanism whereby inhibition controls the sensitivity of different cohorts of RGCs. This can limit and thereby ensure that appropriate signals are carried centrally in scotopic conditions when sensitivity rather than acuity is crucial. ABSTRACT: The responses of rod photoreceptors, which subserve dim light vision, are carried through the retina by three independent pathways. These pathways carry signals with largely different sensitivities. Retinal ganglion cells (RGCs), the output neurons of the retina, show a wide range of sensitivities in the same dark‐adapted conditions, suggesting a divergence of the rod pathways. However, this organization is not supported by the known synaptic morphology of the retina. Here, we tested an alternative idea that the rod pathways converge onto single RGCs, but inhibitory circuits selectively mask signals so that one pathway predominates. Indeed, we found that application of GABA receptor blockers increased the sensitivity of most RGCs by unmasking rod signals, which were suppressed. Our results indicate that inhibition controls the threshold responses of RGCs under dim ambient light. This mechanism can ensure that appropriate signals cross the bottleneck of the optic nerve in changing stimulus conditions.